2013
DOI: 10.1111/ijsw.12020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of policy measures and coaching on the availability and accessibility of early child care: A longitudinal study

Abstract: We conducted a study of changes in the availability, accessibility and enrolment of children from low‐income, single‐parent and ethnic minority families in early child care centres. The study was carried out in Brussels which offers unique possibilities to study accessibility in a context in which quality and costs are controlled across centres. A survey on access policies in 89 day care centres, and on 150 mothers regarding their search process, was complemented by two focus groups attended by centre director… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Other research endeavours focusing on single countries found similar patterns, for instance in the USA (Fuller and Xiaoyan 1996;Meyers et al 2004;Greenberg 2011) and in several European countries (e.g. Abrassart and Bonoli 2015;Krapf 2014;Vandenbroeck et al 2014;Van Lancker and Ghysels 2012;Del Boca and Pasqua 2005;Spieß et al 2003). Only Denmark, Iceland and to a lesser extent Sweden report equity in childcare use amongst young children from different socio-economic backgrounds (Meagher and Szebehely 2012).…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Other research endeavours focusing on single countries found similar patterns, for instance in the USA (Fuller and Xiaoyan 1996;Meyers et al 2004;Greenberg 2011) and in several European countries (e.g. Abrassart and Bonoli 2015;Krapf 2014;Vandenbroeck et al 2014;Van Lancker and Ghysels 2012;Del Boca and Pasqua 2005;Spieß et al 2003). Only Denmark, Iceland and to a lesser extent Sweden report equity in childcare use amongst young children from different socio-economic backgrounds (Meagher and Szebehely 2012).…”
Section: Introductionmentioning
confidence: 76%
“…). Some scholars emphasize the importance of personal preferences in explaining childcare use, but empirical studies have shown how differences in parental preferences are also moulded in differences in availability, as one can hardly desire what is not available (Henley and Lyons ; Vandenbroeck et al ). Yet, even in countries where childcare slots are available as a legal right, such as Sweden or Denmark, not all parents enrol their children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to parents, the study by Vandenbroeck et al (2008Vandenbroeck et al ( , 2014 sheds light on structural quality aspects such as availability, access and enrolment. Over a 5-year period, new municipal policies were developed with financial incentives to enhance the accessibility of child care to children from low-income families, single parent families and ethnic minority families.…”
Section: Collaborative Practicesmentioning
confidence: 99%
“…Enrolment policies can also make a difference to encouraging participation of under-represented groups. In Brussels, all funded centres are required to have an enrolment list in which 20% of children belong to one or more target groups (low-income, single-parent and ethnic-minority families) (Vandenbroeck et al, 2014). Over time, this general policy requirement, coupled with support, has led to a shift in centre directors' attitudes to 'social' access criteria and to tangible increases in participation for the target groups.…”
Section: Funding and Enrolment Policiesmentioning
confidence: 99%